1968
DOI: 10.1139/g68-077
|View full text |Cite
|
Sign up to set email alerts
|

QUANTITATIVE STUDY OF INTRASPECIFIC VARIATION OF DNA PER CELL INPICEA GLAUCAANDPINUS BANKSIANA

Abstract: Intraspecific variation of DNA per cell was established chemically and cytophotometrically for 17 seed sources of Picea glauca, and cytophotometrically for 11 sources of Pinus banksiana. The DNA Feulgen absorption per cell varied from the lowest to the highest amount by factors of 1.6 and 1.5 for Picea glauca and Pinus banksiana, respectively. Intraspecific DNA also varies with intraspecific nuclear volume. Intraspecific variation of histone was similar to the observed DNA variation. A regression analysis betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
2

Year Published

1972
1972
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 19 publications
1
40
0
2
Order By: Relevance
“…This is probably the case of DNA variations in Picea glauca and P. sitchensis (MIKscHE 1968(MIKscHE , 1971) not confirmed by subsequent studies (see BENNETT and SMITH 1976;GREILHUBER 1988).…”
Section: Methods Of Analysismentioning
confidence: 76%
“…This is probably the case of DNA variations in Picea glauca and P. sitchensis (MIKscHE 1968(MIKscHE , 1971) not confirmed by subsequent studies (see BENNETT and SMITH 1976;GREILHUBER 1988).…”
Section: Methods Of Analysismentioning
confidence: 76%
“…1. The ratio of the highest 1C nuclear DNA content to the lowest 1C nuclear DNA content was 1.36, which was lower than the ratio of 1.5, 1.6, 1.7 and 1.9 respectively among the provenances of Pinus banksiana, Picea glauca, Picea sitchensis and Pseudotsuga menziesii (Miksche 1968, 1971, El-Lakany and Sziklai 1971. Dhir and Miksche (1974) observed that the maximum ratio was 2.2 of North red pine (Pinus resinosa) distributed in relatively small geographical distribution.…”
Section: Resultsmentioning
confidence: 76%
“…Xiaoxingan in Northeast, China. Chromosome number of this species was 2n=24 in correspondence with other species in the genus Pinus, but there were some reports showing that considerable intraspecific and interspecific variation of nuclear DNA content in this genus (Miksche 1968, 1971, Price et al 1973, Dhir and Miksche 1974, Teoh and Rees 1976, Dhillon 1980, Dhillon et al 1978, Ohri and Khoshoo 1986, Wakamiya et al 1993, Wyman et al 1997). Ohri and Khoshoo (1986) observed that the 20 Pinus species widely collected from North America, Europe and Eurasia had a 1.73-fold variation in nuclear DNA content, and noted that Pinus species with very high DNA content distributed in temperate and highly xeric habitats.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…As thepH increases above 81 the staining decreases, and at pH's below 80 nuclear specificity is lost (Bloch, 1966). Since the publication of Alfert and Geschwind's authoritative paper, the fast green staining reaction has found increasing favour for quantitative cytochemical estimations of histone amounts (Bhattacharya, Naylor and Shaw, 1965;Himes, 1967;Miksche, 1968;Kirk and Jones, 1970;Kusanagi and Yanagi, 1970;Ayonoadu and Rees, 1971;Diez and Cionini, 1971;Innocenti, 1971;Moore, 1971). There are in addition some instances where a good agreement has been found for variation in histone amounts determined both by cytochemical means and by biochemical methods (John and Jones, 1970;Kirk, 1972).…”
Section: Materials and Methods (A) Materialsmentioning
confidence: 99%